2014
DOI: 10.1155/2014/920123
|View full text |Cite
|
Sign up to set email alerts
|

A Bio-Inspired QoS-Oriented Handover Model in Heterogeneous Wireless Networks

Abstract: We propose a bio-inspired model for making handover decision in heterogeneous wireless networks. It is based on an extended attractor selection model, which is biologically inspired by the self-adaptability and robustness of cellular response to the changes in dynamic environments. The goal of the proposed model is to guarantee multiple terminals’ satisfaction by meeting the QoS requirements of those terminals’ applications, and this model also attempts to ensure the fairness of network resources allocation, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Furthermore, we evaluate the performance of the network selection solution by combining both terminalside and network-side interest, namely, in terms of the global mobile users' QoS satisfaction and the efficiency and fairness of network resource allocation among multiple users. An ASM based network selection method is proposed in [19], where the network selection solution only takes into account the QoS satisfaction perceived at individual terminals. In this paper, we develop a novel dynamic network selection method which not only can satisfy the QoS requirements of different terminal's applications, but also can ensuring the efficient utilization and fair allocation of heterogeneous network resources in a global sense.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we evaluate the performance of the network selection solution by combining both terminalside and network-side interest, namely, in terms of the global mobile users' QoS satisfaction and the efficiency and fairness of network resource allocation among multiple users. An ASM based network selection method is proposed in [19], where the network selection solution only takes into account the QoS satisfaction perceived at individual terminals. In this paper, we develop a novel dynamic network selection method which not only can satisfy the QoS requirements of different terminal's applications, but also can ensuring the efficient utilization and fair allocation of heterogeneous network resources in a global sense.…”
Section: Related Workmentioning
confidence: 99%
“…It is worth pointing out that the (19) also adopts the form of the cumulative product function. From (19), it can be observed that GlobalSatisf action can be treated as a multivariable function which monotonously increases with each M T Satisf action i .…”
Section: T Satisf Actionmentioning
confidence: 99%
“…As shown by the studies [26], the attractor selection mechanism could provide a novel bio-inspired paradigm for achieving a self-adaptive and robust solution in dynamic environments. For specified application contexts of mobile communication, some researchers have successfully applied this bio-inspired mechanism to design a multi-path routing protocol in overlay networks [27], improve the robustness of a AODV-like routing protocol in MANETs [28], and build handover model in heterogeneous wireless networks [29]. In this paper, we integrate the attractor selection into the proposed epidemic broadcasting for the enhancement of routing performance in VANETs in terms of robustness and adaptability.…”
Section: Related Workmentioning
confidence: 99%
“…Some existing work has already revealed the power of the attractor selection to induce some solution designs of more scalability, adaptability and robustness for specified computer networking problems [27,28,29]. Based on the high-dimensional attractor selection model defined in [29], we propose an adaptive and robust message dissemination method for VANETs. Firstly, we present the adopted attractor selection model as the following differential equations:…”
Section: Preliminaries Of Attractor Selection Modelmentioning
confidence: 99%
See 1 more Smart Citation